2002
DOI: 10.1142/s0218625x02002099
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Spectrum of Ozone in the 105–200 Nm Wavelength Region

Abstract: Excited states of ozone are investigated based on the absorption spectrum measured in the wavelength region 105-200 nm. Two Rydberg series corresponding to the transition 6a1 → ns, np and 4b2 → ns and np were assigned for the most of the strong peaks in the absorption spectrum. In 112-105 nm wavelengths, the progression of vibrational bands with an energy spacing of about 622 cm −1 was measured which was unknown before.Surf. Rev. Lett. 2002.09:125-128. Downloaded from www.worldscientific.com by MCGILL UNIVERSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Ozone is the most important UV absorber of all oxygen species. Watanabe et al [18] have measured the ozone UV absorption spectrum over the spectral range of 100-220 nm, and Tu and Nee [26] over the range of 105-200 nm. Ozone absorbs strongly UV radiation entering the MLT layer.…”
Section: Absorption Of Uv Visible and Ir Radiation By Oxygen Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozone is the most important UV absorber of all oxygen species. Watanabe et al [18] have measured the ozone UV absorption spectrum over the spectral range of 100-220 nm, and Tu and Nee [26] over the range of 105-200 nm. Ozone absorbs strongly UV radiation entering the MLT layer.…”
Section: Absorption Of Uv Visible and Ir Radiation By Oxygen Speciesmentioning
confidence: 99%
“…When ozone is photolyzed by photons of visible light, λ< 611nm, are produced O 2 (a 1 ∆ g ) + O( 3 P). With UV photons λ < 310 nm, the products are O 2 (a 1 Tu and Nee [26] suggested that when a UV photon at the wavelength λ = 121.6 nm dissociates ozone, the result is direct formation of three oxygen atoms from one ozone molecule: . So between the wavelengths of 118.6 to 121.6 nm there is a window in which three oxygen atoms are formed from one ozone molecule.…”
Section: Ozone Photolysis and Reactions Thereofmentioning
confidence: 99%